Review of the genus Eotilla Schuster, 1949 (Hymenoptera: Bradynobaenidae: Typhoctinae: Eotillini) and description of new species from Argentina - Torréns, Javier; Fidalgo, Patricio; Roig-Alsina, Arturo; Brothers, Denis J. (Zootaxa, 2014)
Diagnoses for the genus Eotilla Schuster, 1949 based on males and females, new generic and specific characters, descriptions of two new Argentinian species (Eotilla schusteri Torréns, Fidalgo, Roig-Alsina & Brothers, sp. nov. and E. medanito Torréns, Fidalgo, Roig-Alsina & Brothers, sp. nov., based on both sexes), a description of the female of E. superba Brothers, 1974 and redescriptions of the males of E. mickeli Schuster, 1949 and E. superba are provided. A key to the species of Eotilla is presented.